The prototype of A Forklift Robot Based on AGV System and Android Wireless Controlled for Stacked Shelves - 1 (Informatics Department-Universitas Dr. Soetomo, 2020)
The paper aims to build a prototype of an automatic forklift robot that can collect and place goods in the stacking shelves, that are monitored remotely using an Android-based device. The method used is AGV (Automated Guided Vehicle) on this forklift robot prototype to adjust its positions, by following a line that preset trajectory for stacking shelf positions, where this forklift robot can collect and place goods. The robot navigation system uses a photodiode for the line follower system, and for storage of goods, it uses the proximity sensors detecting the presence of goods on miniature stacking goods and decide where it can store a good or not on that designated cell of the stacking shelf. The miniature of stacking shelves is two by three cells. The control of the robot has two input controllers. One is on a robot itself. The other was on handheld based on Android operating systems, which control remotely using the wireless system with Bluetooth protocol. The results of the discussion on paper, the forklift robot could manage the task given as the predefined line to a followed parameter of stacking shelves with two by three-stack configuration for collect and place goods into their positions, the average time for the robot to collecting and placing goods on stacking from standing still position to stacking shelf then back to the robot origin position. It resulted in the shortest processing time around 43 seconds and the longest time around 45,3 seconds from the start position to stacking shelf position.